MITIGASI BENCANA TSUNAMI DI WILAYAH PESISIR LAMPUNG - Dwi Jokowinarno (UNIVERSITAS LAMPUNG, 2011)
Disaster management is a dynamic process, integrated and sustainable effort to increase quality of preventive, preparedness,mitigaton, emergency response, evacuation and reconstruction. Mitigation is strategy to reduce and minimize negative impact of disaster. At least, there are six strategies in tsunami mitigation. Firstly, to protect living, infrastructure and coastal zone environment. Secondly, to increase understanding and participation in mitigation of tsunami. Third, to increase preparedness and awareness of upcoming disaster. Fourth, to increase coordination and institution capacity. Fiveth, to establish law enforcement that can be efective to realize disaster mitigation by mean of making code of conduct that regulate mitigation implementation, to develop guidance of planning and implemetation of disaster protection. Sixth, to push sustainability of economic activity and increasing social wellfare, security, and confort in coastal zone area.